Law in the Margins: economies of Illegality and Contested Sovereignties - Aliverti, Ana (The British journal of criminology, 2023)
Liberal theory has long fetishized state law as a fortress against disorder, anarchy, and private violence. To prevent violence writ large, it advocated, the nation-state should be endowed with its monopoly, as the impartial and rational guardian of civilization and social peace. Yet, as critics suggest, the normative binary of law/violence and the legal purity of the state is empirically untenable and, as such, remains an ideological construct sustained and perpetuated through law and its fictions. In this paper, I revisit these debates to reflect on legal fictions in the context of migration policing. I draw on ethnographic research I conducted with immigration and police officers in the UK. Amid the growing economies of illegality that rely on migrant labour which these officers are in charge of suppressing, their everyday work reveals spaces of legal murkiness and ambiguity. The paper explores the paradoxes, dilemmas and contradictions that such legal ambiguity gives rise to and their implications for state sovereignty.